Tribo-piezoelectricity in Janus transition metal dichalcogenide bilayers: A first-principles study. (February 2019) - Cai, Haifang; Guo, Yufeng; Gao, Huajian; Guo, Wanlin
Abstract: Semiconducting Janus transition metal dichalcogenides (TMDs) are attractive for application in nanoscale electricity harvesting devices as their strong out-of-plane piezoelectricity. Here our extensive first-principles calculations reveal that in-plane interlayer sliding of Janus MXY (M = Mo or W, X/Y = S, Se, or Te, and X ≠ Y) bilayers would lead to significant enhancement of vertical piezoelectricity. The tribo-piezoelectric transduction mechanism is elucidated by tribological energy conversion of Janus TMD bilayers overcoming interlayer sliding resistance to reach the A-A stacking states that have the strongest out-of-plane piezoelectricity. Reducing interlayer distances of Janus TMD bilayers increases sliding energy barriers, and accordingly improves vertical charge polarization and inductive voltage generated between the top and bottom surfaces of Janus TMD bilayers. Based on the presented tribo-piezoelectricity, a compression-sliding design strategy is proposed for Janus TMD bilayers to create novel nanogenerators. Graphical abstract: Highlights: In-plane interlayer sliding of Janus TMD bilayers would lead to significant enhancement of vertical piezoelectricity. A novel tribo-piezoelectric effect is revealed for Janus TMD bilayers. The compression-sliding design strategy is proposed for Janus TMD bilayers to create nanogenerators with high power densities.